Tailoring of neurosurgical ablative procedures in the management of refractory cancer pain. Issue 9 (September 2020) - Hochberg, Uri; Berger, Asaf; Atias, Miri; Tellem, Rotem; Strauss, Ido
Abstract : Introduction: Neurosurgical ablative procedures can offer immediate and effective pain relief for patients suffering from refractory cancer pain. However, choosing the appropriate procedure for each patient may not be straightforward and warrants an interdisciplinary approach. The purpose of the current study was to evaluate the outcome of patients with cancer who were carefully selected for neurosurgical intervention by a dedicated interdisciplinary team composed of a palliative physician and nurse practitioner, a pain specialist and a neurosurgeon. Methods: A retrospective review was carried out on all patients who underwent neurosurgical ablative procedures in our institute between March 2015 and September 2019. All patients had advanced metastatic cancer with unfavorable prognosis and suffered from intractable oncological pain. Each treatment plan was devised to address the patients' specific pain syndromes. Results: A total of 204 patients were examined by our service during the study period. Sixty-four patients with localized pain and nineteen patients with diffuse pain syndromes were selected for neurosurgical interventions, either targeted disconnection of the spinothalamic tract or stereotactic cingulotomy. Substantial pain relief was reported by both groups immediately (cordotomy: Numerical Rating Scale (NRS) 9 ≥1, p=0.001, cingulotomy: NRS 9 ≥2, p=0.001) and maintained along the next 3-month follow-up visits. Conclusions: An interdisciplinary collaboration designated to provide neurosurgical ablative procedures among carefully selected patients could culminate in substantial relief of intractable cancer pain. Trial registration number: IR0354-17.